Characterization of the growth of Pseudomonas sp. strain DrY135 on acrylamide - Rahman, Mohd Fadhil; Khayat, Mohd Ezuan; Mohd Yakasai, Hafeez; Yasid, Nur Adeela; Shukor, Mohd Yunus (Hibiscus Publisher, 2022)
This study investigated the growth properties of a molybdenum-reducing bacteria previously isolated for its ability to break down amides. The bacterial growth range is 500–1000 mg/L, 6.5–8.0 pH, and 30–35 °C. The presence of hazardous heavy metals such as mercury, silver, and copper impeded this bacterium's development on acrylamide. The protracted lag phase seen when growing on acrylamide demonstrates the compound's severe growth inhibition. This bacterium has the potential to be an effective acrylamide bioremediation agent due to its greater tolerance for acrylamide than other acrylamide-degrading bacteria identified in the scientific literature. The influence of initial pH on bacterial growth at room temperature indicates that the optimal pH range lies between 6.5 and 8.0. The ideal temperature range for plant growth was between 30 and 35 oC. In a series of experiments utilizing a starting concentration of 1% (w/v) of various organic carbon sources, it was determined that glucose supported the most cellular growth on acrylamide, followed by sucrose, fructose, mannose, and citrate, in descending order of efficiency, whereas mannitol did not support growth. Doses of 300 and 500 mg/L of acrylamide stimulated the most rapid growth expansion, but concentrations of 1500 mg/L and above completely halted development. Copper (Cu), lead (Pb), cadmium (Cd), chromium (Cr), and mercury (Hg) were investigated at a concentration of 2 ppm. Mercury hindered growth by 71 percent, copper by 72 percent, and cadmium by 52 percent, according to our findings. There was a linear association between the acrylamide content and the delay before this bacterium began to develop. A lag time of one to three days was found when the acrylamide content grew from 100 to 1,500 mg/L. As quantities of acrylamide increased, so did the maximal growth rate, indicating an overall pattern of increasing toxicity.